Virtual reality‐based cognitive‐motor training for middle‐aged adults at high Alzheimer's disease risk: A randomized controlled trial. Issue 1 (26th March 2018) - Doniger, Glen M.; Beeri, Michal Schnaider; Bahar‐Fuchs, Alex; Gottlieb, Amihai; Tkachov, Anastasia; Kenan, Hagar; Livny, Abigail; Bahat, Yotam; Sharon, Hadar; Ben‐Gal, Oran; Cohen, Maya; Zeilig, Gabi; et al.
Abstract: Introduction: Ubiquity of Alzheimer's disease (AD) coupled with relatively ineffectual pharmacologic treatments has spurred interest in nonpharmacologic lifestyle interventions for prevention or risk reduction. However, evidence of neuroplasticity notwithstanding, there are few scientifically rigorous, ecologically relevant brain training studies focused on building cognitive reserve in middle age to protect against cognitive decline. This pilot study will examine the ability of virtual reality (VR) cognitive training to improve cognition and cerebral blood flow (CBF) in middle‐aged individuals at high AD risk due to parental history. Methods: The design is an assessor‐blind, parallel group, randomized controlled trial of VR cognitive‐motor training in middle‐aged adults with AD family history. The experimental group will be trained with adaptive "real‐world" VR tasks targeting sustained and selective attention, working memory, covert rule deduction, and planning, while walking on a treadmill. One active control group will perform the VR tasks without treadmill walking; another will walk on a treadmill while watching scientific documentaries (nonspecific cognitive stimulation). A passive (waitlist) control group will not receive training. Training sessions will be 45 minutes, twice/week for 12 weeks. Primary outcomes are global cognition and CBF (from arterial spin labeling [ASL]) at baseline, immediately after training (training gain), and 3 months post‐training (maintenance gain). We aim to recruit 125 participants, including 20 passive controls and 35 in the other groups. Discussion: Current pharmacologic therapies are for symptomatic AD patients, whereas nonpharmacologic training is administrable before symptom onset. Emerging evidence suggests that cognitive training improves cognitive function. However, a more ecologically valid cognitive‐motor VR setting that better mimics complex daily activities may augment transfer of trained skills. VR training has benefited clinical cohorts, but benefit in asymptomatic high‐risk individuals is unknown. If effective, this trial may help define a prophylactic regimen for AD, adaptable for home‐based application in high‐risk individuals.